E-Village Management System (EVMS) - Latif, Nur Azimah (Universiti Teknologi Petronas, 2006)
This paper reports that the functionality and usability of the online system on the internet. The web technology delivers the promise of access to information from anywhere in the world. The purpose of this project called is to integrate the online approaches to a Residential College Registration and helps their staff to organize the data and information into better style and format. The methodology used to develop the system for the whole project until it complete will be software process development. It starts from analysis phase where it need to analyze the current system and problem statement that occurred. The scope of this study is to ensure there is no more data redundancy, reduce delay response time to acquire an information and easy access to register rooms. In other view, it would help management staff mainly to analyze the data, update records, searching and deleting records and maintaining the information. The result of this study is the importance of online system related to a management and admission in a large organization especially universities. The report concludes on a rather critical view of the importance of online system, as well as the author's own stand in the midst of debate. Next, will be the shortcomings and recommendation that author makes with regard to the project.